2022
DOI: 10.31234/osf.io/j87pn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Descriptive norms caused increases in mask wearing during the COVID-19 pandemic

Abstract: Human sociality is governed by two types of social norms: injunctive social norms, which prescribe what people ought to do, and descriptive social norms, which reflect what people actually do. These norms enable people to cooperate in the face of group-wide challenges. While previous experimental work has shown that people’s behavior is influenced by social norms, several open questions remain about the natural emergence of injunctive and descriptive social norms within populations and their causal influences … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Healthcare institutions are by the nature of their responsibility to protect health 190,41,191,192 as well as the high levels of physical contact and concentrations of both vulnerable and COVID infected individuals-locations in which enhanced protections should be normalized. This includes multiple levels of precautions: the universal use of N95 or better respirators 193,194,195,196 , high frequency testing, enhanced air hygiene, and optimized physical and social distancing. Some healthcare systems are already consistently implementing 197 or reintroducing such measures 198 .…”
Section: The Role and Responsibility Of Healthcare Professionals And ...mentioning
confidence: 99%
“…Healthcare institutions are by the nature of their responsibility to protect health 190,41,191,192 as well as the high levels of physical contact and concentrations of both vulnerable and COVID infected individuals-locations in which enhanced protections should be normalized. This includes multiple levels of precautions: the universal use of N95 or better respirators 193,194,195,196 , high frequency testing, enhanced air hygiene, and optimized physical and social distancing. Some healthcare systems are already consistently implementing 197 or reintroducing such measures 198 .…”
Section: The Role and Responsibility Of Healthcare Professionals And ...mentioning
confidence: 99%
“…However, only a limited number of studies have examined the bi-directional associations between mask usage and beliefs regarding the associated reasons. A recent longitudinal study over a 2-year period beginning in the fall of 2020 in the Unites States showed significant bi-directional associations between mask usage and norms 15 . Therefore, examining the associations between the two entities before and after the downgrading of the legal status of COVID-19 in Japan from a bidirectional perspective would be crucial in developing strategies not only to promote infection prevention measures in another outbreak of COVID-19 or an emergent infectious disease outbreak, but also in mitigating mask usage.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, individual trust and beliefs about vaccination decisions of others can play a relevant role in overcoming vaccine hesitancy. By examining individual trust towards vaccination decisions of other society members, we add to the literature investigating the role of prosocial motivations in health preventive behavior [44][45][46] .…”
mentioning
confidence: 99%